The survival of understorey birds in the Tropical Rainforest of Ziika, Uganda - Dranzoa, Christine (Journal of African Ornithology, 1997)
The forests at the shores of Lake Victoria had considerable attention from researchers during the 1970s. Ziika forest is one of the many small forest fragments that fringe the northern part of the lake. This 12 ha forest is surrounded by different habitats, giving it the appearance of a terrestrial 'island'. Birds were first ringed here from September 1970-July 1972. A follow-up was made in 1988-89, during which 186 birds from 27 different species were ringed. Five years later, survival rates were found to be significantly higher than the expected. Some species appeared to survive better than others. There are various assumptions made in estimating survival rates of understorey birds.
Keywords: Understorey birds; Tropical Rainforest; Ziika